Pioneering new perspectives in the fashion industry : disruption, diversity and sustainable innovation - Ritch, Elaine L.; Canning, Catherine; McColl, Julie (Emerald Publishing Limited, 2023)
Amidst an increasingly conscious consumer market, the fashion industry now faces more external pressures than ever. Highlighting new advances that are responsive to societal concerns while still maintaining commerciality and innovation, Pioneering New Perspectives in the Fashion Industry: Disruption, Diversity and Sustainable Innovation examines critical new perspectives on the fashion marketplace that have been driven by both technological advances and widespread concerns over climate change. The editors bring together leading experts who employ empirical research and industry case studies to assess a wide range of issues and developments within the fashion industry, including: Climate activism Diversity, inclusivity and equality Online resale and e-commerce Collective action Fashion influencer brands Circularity Neurodiverse retail experiences Childrenswear Buyer-supplier relations Modest fashion Industry challenges in Sub-Saharan Africa Fashion and technology Vintage consumption Tailored for fashion student use and equally relevant for fashion professionals, Pioneering New Perspectives in the Fashion Industry: Disruption, Diversity and Sustainable Innovation presents a ground-breaking, comprehensive and cutting-edge analysis of the challenges and opportunities changing and reshaping the global fashion industry.